2018
DOI: 10.1021/acs.jpcb.8b08380
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Level Interpretation of Vibrational Spectra of Ordered Ice Phases

Abstract: We build on results from our previous investigation into ice Ih using a combination of classical many-body molecular dynamics (MB-MD) and normal mode (NM) calculations to obtain molecular level information on the spectroscopic signatures in the OH stretching region for all seven of the known ordered crystalline ice phases. The classical MB-MD spectra are shown to capture the important spectral features by comparing with experimental Raman spectra. This motivates the use of the classical simulations in understa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 96 publications
3
50
0
Order By: Relevance
“…We also found “rigid network” modes in ice VIII and VII [2] and “isolated stretching” modes in ice XIV [12]. According to our series of investigations of ice phases, we identified two intrinsic categories of molecule vibrations in the translational band that constitute two sharp peaks [2,12,13,14,15]. In this paper, we confirm the presence of cluster vibrations in a much lower region of the translation band.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…We also found “rigid network” modes in ice VIII and VII [2] and “isolated stretching” modes in ice XIV [12]. According to our series of investigations of ice phases, we identified two intrinsic categories of molecule vibrations in the translational band that constitute two sharp peaks [2,12,13,14,15]. In this paper, we confirm the presence of cluster vibrations in a much lower region of the translation band.…”
Section: Introductionsupporting
confidence: 62%
“…For theoretical investigations of vibrational modes, the most interesting results were those of Whale et al, who found exotic “rigid network” molecular vibrations in the translation band and “isolated stretching” modes of atomic vibrations in the stretching band [8]. We also found “rigid network” modes in ice VIII and VII [2] and “isolated stretching” modes in ice XIV [12]. According to our series of investigations of ice phases, we identified two intrinsic categories of molecule vibrations in the translational band that constitute two sharp peaks [2,12,13,14,15].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, we noticed that Moberg et al used two methods to calculate the Raman spectra, which are many-body molecular dynamics (MB-MD) and normal mode (NM). 12 According to their work, two main Raman peaks were calculated at 3154 and 3243 cm –1 . Furthermore, our results were at 3177 and 3285 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…20,21 Raman spectra calculated for the antiferroelectric structure by DFT 14 are ''in essential agreement with experimental spectra of ice XV'', and so are the calculated structures for this structure by MB-MD. 22 This explanation leaves some room for speculation, which prompted Gasser et al to investigate the influence of pressure and cooling rate on H-ordering quantitatively and systematically. 1 By combining X-ray, differential scanning calorimetry (DSC), Ramanand dielectric relaxation spectroscopy experiments they identified a different cause for the complex behaviour that was not observed for any other ice polymorph before.…”
Section: Introductionmentioning
confidence: 99%